2003
DOI: 10.1159/000073318
|View full text |Cite
|
Sign up to set email alerts
|

Species-Typical Patterns of Infant Contact, Sleeping Site Use and Social Cohesion among Nocturnal Primates in Africa

Abstract: This paper provides a checklist and summary of what is currently known of the variation in infant contact, sleeping site preference and aspects of social cohesion in the nocturnal primates of Africa. Genera and species are compared, based on previously unpublished field observations and a review of the literature. There is a clear pattern of similarity between the species within each genus and distinct differences between genera. Species in the same genus tend to be ecologically equivalent and replace each oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 43 publications
1
73
1
Order By: Relevance
“…This is in contrast to other lorisines, which sleep alone or in mother-infant pairs (e.g. Perodicticus potto and Nycticebus coucang) [Wiens, 2002;Bearder et al, 2003;Pimley, 2003]. Captive male L. l. nordicus maintained in stable family groups have also expressed interest in newborns, and males and older offspring sometimes carry them.…”
Section: Discussionmentioning
confidence: 95%
“…This is in contrast to other lorisines, which sleep alone or in mother-infant pairs (e.g. Perodicticus potto and Nycticebus coucang) [Wiens, 2002;Bearder et al, 2003;Pimley, 2003]. Captive male L. l. nordicus maintained in stable family groups have also expressed interest in newborns, and males and older offspring sometimes carry them.…”
Section: Discussionmentioning
confidence: 95%
“…The potto Perodicticus potto edwardsi, a quadrupedal primate, spent most of its time in the upper canopy (20 to 40 m), but was spotted as low as 5 m, and was found on large branches and lianas (Charles-Dominique 1977). Other researchers have had similar results, indicating that height preference can be an outcome of locomotion or ecological needs (Harcourt & Nash 1986, Fleagle 1999, Heymann & Buchanan-Smith 2000, Pimley 2002, Bearder et al 2003.…”
Section: Microhabitat Variability and Niche Divergencementioning
confidence: 59%
“…Group vigilance may be important by day [Shultz et al, 2004;Shultz and Finlayson, 2010], and by night, for example, tarsiers engage in alarm calling and mobbing in response to raptors and civets [Gursky, 2007]. As Bearder et al [2003] observed, several small, nocturnal primates adopt a lifestyle of solitary living and group sleeping (e.g. G. demidovii and G. moholi ) presumably being difficult to detect when foraging and moving singly at night, but benefitting from sociality, perhaps including a reduced risk of predation, when sleeping in communal nests during daylight.…”
Section: Discussionmentioning
confidence: 99%
“…2 kg), are generally solitary foragers [Bearder, 1987], and the arboreality characteristic of all nocturnal primates may also result in the avoidance of predators that hunt on the ground. Small size enables nocturnal primates not only to be cryptic by night, but to hide by day, whether alone or in company [Bearder et al, 2003]. By night, some species are agile (nocturnal lemurs, galagos and tarsiers) and can make rapid escape, whereas sluggish ones (lorises and pottos) may supplement crypsis with specialised defence (e.g.…”
Section: Introductionmentioning
confidence: 99%